Transaction cost in PPPs project: exploration of influence factors for both public and private sectors in different countries with whole life cycle. Issue 5 (March 2019) - Zhao, Jinpeng
Abstract: The transaction cost in Public-Private Partnerships (PPPs) project is an inevitable issue due to the long-term contract and complex interests. This research aims to explore the influence factors of transaction cost via public or/and private perspectives with developed and developing economics in the whole project life cycle. Literature review is adopted as the research method to study the transaction cost issue and provide a new perspective of transaction cost via distinguishing private and public sector in PPPs project. The research finds that the influence factors of transaction cost exist from preparation phase to operation phase, which include the following 11 dimensions: Improper allocation of risks; Lack of enough experience and knowledge for government staffs; Ex-post assessment; Lack of complete standards and regulations; Design flaw; PPPs' inherent character; Government condition; Quality of project brief; Government's serious investigation; Investment climate; Integrity and enforcement of contract. The research finds that, in different economics, the above 11 factors impact public and private sector in distinct way, and by understanding the factors how to influence the transaction cost will help PPPs participations manage and control the potential cost and risk better.